Associations between genetic HPV 16 diversity and cervical cancer prognosis - Patrícia Patury; Fabio B. Russomano; Miguel Angelo Martins Moreira; Nádia R. C. Kappaun; Liz Maria de Almeida; Raquel B. M. Carvalho; Luís Felipe. L. Martins (PLoS ONE, 2025)
Introduction Cervical cancer (CC) arises as a result of chronic and persistent female infection by different oncogenic human papillomaviruses (HPV). The incidence of this disease is still high in developing countries, such as Brazil, where diagnosis is often made in advanced stages. HPV 16 is the most common Papillomavirus genotype in CC worldwide. Studies regarding the association of different HPV 16 lineages with overall and disease-free CC survival rates can contribute to further understanding the behavior of different HPV 16 lineages concerning the prognosis of CC cases. Objective To assess the CC prognosis of patients treated in a Brazilian institution concerning HPV16 lineages. Methods Data were obtained from a prospective cohort of 334 patients with CC recruited between July 2011 and March 2014 and treated at the Brazilian National Cancer Institute (INCA), in Rio de Janeiro, Brazil. HPV 16 lineages were identified in tumor tissue samples. Genetic HPV 16 diversity comprised 218 cases of lineage A, 10 of lineage B, 10 of lineage C, and 96 of lineage D. In addition to HPV 16 lineages, age, histopathological type, staging, and treatment completion were evaluated as predictors of CC prognosis. Results The median patient age was 48 years. The most common histopathological type was squamous cell carcinoma (82.3%), followed by adenocarcinoma. Locally advanced disease staging was the most frequently detected, represented by similar stage II and III percentages (36.2% and 37.7%), followed by initial stage I (19.2%) and stage IV (6.9%). Two hundred two patients completed CC treatment. Age, histological type, staging, and treatment completion were associated with a higher risk of death, which was not observed for the HPV 16 lineage variable. With regard to age, an increase in each year of life led to approximately a 1% increase in the risk of death. Other histopathological types (poorly differentiated carcinoma, adenosquamous, neuroendocrine, and sarcoma) were associated with a higher risk of death compared with adenocarcinoma. Patients diagnosed in advanced stages exhibited a higher risk of death, and those who did not complete treatment exhibited an over 2-fold increased risk of death. Conclusion This study found no associations between HPV 16 lineages A, B, C, and D and CC prognosis.